2021
DOI: 10.1080/22221751.2020.1863747
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 genomic characterization and clinical manifestation of the COVID-19 outbreak in Uruguay

Abstract: COVID-19 is a respiratory illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and declared by the World Health Organization a global public health emergency. Among the severe outbreaks across South America, Uruguay has become known for curtailing SARS-CoV-2 exceptionally well. To understand the SARS-CoV-2 introductions, local transmissions, and associations with genomic and clinical parameters in Uruguay, we sequenced the viral genomes of 44 outpatients and inpatients in a private he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 52 publications
6
28
0
2
Order By: Relevance
“…The frequency of S protein 614G was significantly associated with high fatality rates in several countries, as reported in studies which analyzed SARS-CoV-2 sequences from GISAID database [8,10,11]. However, clinical studies showed that this mutation did not correlate with severity of COVID-19, including mortality, transfer to ICU, mechanic ventilation, or length of stay at hospital [30,37,41,42,44,45].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The frequency of S protein 614G was significantly associated with high fatality rates in several countries, as reported in studies which analyzed SARS-CoV-2 sequences from GISAID database [8,10,11]. However, clinical studies showed that this mutation did not correlate with severity of COVID-19, including mortality, transfer to ICU, mechanic ventilation, or length of stay at hospital [30,37,41,42,44,45].…”
Section: Discussionmentioning
confidence: 81%
“…A clinical study by Long et al showed that infection with SARS-CoV-2 variants harboring the D614G substitution was not associated with disease severity, overall mortality, transfer to ICU, mechanical ventilation and length of stay at hospital [41]. This result was supported by other research [33,45]. In a study conducted among 44 Vietnamese patients, 85 mutations covering 67 variant types were reported, of which P323L and D614G variants were the most frequent (present in 40/44 patients), followed by C241U (39/44) and GGG to AAC at 28881-3 variants (33/44).…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 74%
See 2 more Smart Citations
“…En Uruguay, el análisis genético muestra que los clados S y G (G, GH, GR) dominan, representando más del 90% de las cepas del virus en nuestro estudio; el resultado fatal de la infección por SARS-CoV-2 está significativamente relacionado con la hipertensión, Insuficiencia renal e ingreso en UCI (FDR <0,01), pero no hay mutaciones en proteínas estructurales o no estructurales como la proteína pico D614G (12) . Al igual que en Perú, países de Norteamérica como Canadá ha rastreado al clado GR con mayor frecuencia, seguidos de los clados G y GH, y en menor frecuencia los clados S y L, estos últimos fueron identificados en la misma frecuencia en Estados Unidos, no obstante, en este país se ha identificado con más frecuencia al clado GH seguidos de los clados GR y G; en México, no ocurre lo mismo, ya que los clados más frecuentes son GR y G seguido del GH, siendo igual en el caso de los clados S y L siendo muy menores, además de que en esta parte del continente americano se encontraron los clados O y V (11) .…”
Section: Discussionunclassified